Pengaruh Model Pembelajaran Berbasis Proyek dan Kemampuan Berfikir Kreatif: Terhadap Hasil Belajar IPS Siswa Kelas IV Sekolah Dasar - Parihah, Ihah; Rosita, Tita; Saabighoot, Yus Alvar; Houtman, Houtman (Nuansa Akademik: Jurnal Pembangunan Masyarakat, 2023)
The purpose of the study was to obtain information about the effect of using project-based learning models and creative thinking skills on social studies learning outcomes. The research was conducted at SDN Tigaraksa IV. The population is 130 students with a sample of 64 respondents. The instruments used are questionnaires and tests. Data analysis using T-test. The threshold value of Sig to determine the magnitude of the influence of the learning model is 0.000 <0.05 and the tcount is 4.083 <ttable 2.738. The threshold value of Sig creative thinking ability and student learning outcomes is 0.000 < 0.05 and the tcount value is 43.186 < t table 2.738 with a significant value between variables on student learning outcomes of 0.000 < 0.05 and the F arithmetic value is 1865,006> 4,150. The results of the analysis show that there is an influence between project-based learning and creative thinking skills on student learning outcomes